The influence of strategies on the entrance exam to the University in the mathematical skills of engineering students - Nieto Isidro, Susana; Martínez Abad, Fernando; Rodríguez Conde, María José (Revista Complutense de Educación, 2016)
It is analyzed what is the initial level of knowledge of Calculus for 402 students who access to university degrees on engineering during the academic years 2011-2012, 2012-2012-2013 and 2013-2014. These differences are classified taking into account their way of entrance of the students and their strategy facing the mathematics examination included into the current Spanish Access to University Examination (PAU). From the results of an anonymous questionnaire has been designed by the authors, it has been determined the presence of four significant groups of freshman students. The first group correspond to the students who have overcome the specific mathematics test of the PAU; a second group correspond to the students who have not passed this test in the PAU; the third group is formed by the students who have avoided this examination, and finally the fourth group is constituted by the students coming from Vocational Training Modules. Through the use of non-parametric analysis (analysis post-hoc based in Kruskal-Wallis’ contrast), it has been determined that these four groups show a level of Calculus knowledge which is significantly different. This situation affects to the teacher’s labor because it supposes an important didactic adaptation along the mathematical subjects during the first academic year to improve these poor basic mathematical skills.
Keywords: initial test; previous knowledge; access to the University; mathematics; engineering education